Celebrating 40 years of ICT in libraries, museums, and archives : institutional repositories. (Program (Belfast, Northern Ireland), 2006)
This e-book explores issues related to the development of Institutional Repositories. The articles present a range of international perspectives and experiences, including the background to the open access movement and the views of the UK's Joint Information Systems Committee on digital preservation. Technical aspects are explored through a case study on the development of an Institutional Repository and consideration of the challenges of personal name identification in repositories.